Sorting and recycling endosomes - Guo, Wei; ScienceDirect eBooks (Amsterdam : Academic Press is an imprint of Elsevier, 2015)
Sorting and Recycling Endosomes provides the latest information on endosomes, the receiving compartment for endocytosed cargos, and the donor compartment and sorting station for cargos designated to lysosomes, Golgi, or plasma membrane. In recent years, the importance of endosomes as a sorting and recycling compartment has become increasingly appreciated. As such, scientists from various fields of cell biology, membrane traffic, and beyond, see the needs to communicate and learn about the methods used to investigate the dynamics and functions of endosomes. This book brings together specialists from the field who contribute their expertise on a broad range of biomedical topics that will provide ideal reading for researchers interested in endosomal sorting and recycling. This volume covers the approaches necessary to study the key components that mediate the generation and transport of membrane-bounded carriers from the endosomes, and how membrane trafficking machinery is coordinated with cytoskeletons during these processes. In addition to studies carried out in mammalian cells, other model systems such as worm and yeast are also included.
2.1 Cloning of MoRab11, MoRab8, and MoRab12.1.1 Extraction of total RNA from the M. oryzae strain Guy11; 2.1.2 Amplifying the cDNAs of MoRab11, MoRab8, and MoRab1 by RT-PCR and cloning into the bidirectional expression vector pBI-Tet ...; 2.2 Expression and Intracellular Localization of MoRab11, MoRab8, and MoRab1; 2.2.1 Transfection of BHK-21 cells; 2.2.2 Immunoblot analysis of protein expression; 2.2.3 Localization by confocal fluorescence microscopy; Summary; Acknowledgments; References; 4. Methods to analyze novel liaisons between endosomes and centrosomes
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed September 11, 2015).
Elsevier
Keywords: Endosomes; Cell interaction; SCIENCE / Life Sciences / Anatomy & Physiology; Cell interaction; Endosomes; Endosomes; Electronic books